2018
DOI: 10.1007/s10484-018-9394-4
|View full text |Cite
|
Sign up to set email alerts
|

Neuromodulating Attention and Mind-Wandering Processes with a Single Session Real Time EEG

Abstract: Our minds are continuously alternating between external attention (EA) and mind wandering (MW). An appropriate balance between EA and MW is important for promoting efficient perceptual processing, executive functioning, decision-making, auto-biographical memory, and creativity. There is evidence that EA processes are associated with increased activity in high-frequency EEG bands (e.g., SMR), contrasting with the dominance of low-frequency bands during MW (e.g., Theta). The aim of the present study was to test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 35 publications
2
15
0
Order By: Relevance
“…The objective of this trial was to explore if 10 repeated sessions of 2 neurofeedback protocols were effective in increasing and inhibiting SMR or Theta bands and, consequently, modulate sustained and mind-wandering attention, in healthy volunteers. Overall, confirming previous findings, 5 both protocols increased the amplitude of the up-trained bands (either SMR or Theta) but failed to decrease the amplitude of down-trained bands, particularly for Theta in the SMR⇑Theta⇓ protocol. A previous study found that this was also the case in a single session protocol.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The objective of this trial was to explore if 10 repeated sessions of 2 neurofeedback protocols were effective in increasing and inhibiting SMR or Theta bands and, consequently, modulate sustained and mind-wandering attention, in healthy volunteers. Overall, confirming previous findings, 5 both protocols increased the amplitude of the up-trained bands (either SMR or Theta) but failed to decrease the amplitude of down-trained bands, particularly for Theta in the SMR⇑Theta⇓ protocol. A previous study found that this was also the case in a single session protocol.…”
Section: Discussionsupporting
confidence: 89%
“…In another study, using a similar protocol, we confirmed the difficulty in selectively inhibiting Theta in 1 single session training protocol. 5 The objective of the current trial was to test if we could possibly reverse this effect in a multiple sessions training as suggested by other studies. 7 Apparently this was not the case.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The users can utilize these signals learn to regulate their brain activity and in return improve their executive (Enriquez-Geppert et al, 2013), mental flexibility (Enriquez-Geppert et al, 2014), and attentional abilities (Egner and Gruzelier, 2001) as well as enhance their task engagement (Egner and Gruzelier, 2004). However, the effects of this approach on mind wandering remain unclear (Gonçalves et al, 2018). Transcranial direct current stimulation (tDCS) represents a technique of neuromodulation that can be used to boost executive functioning (see Callan and Perrey, 2019;Cinel et al, 2019).…”
Section: Neuro-adaptation Of the End-user(s)mentioning
confidence: 99%
“…Evidently, the published results to date are variable. For example, Gadea et al [66] [67][68][69] reported successful voluntary modulation of brain activity (change in the EEG signal) but no effects on the behavior (eg, symptom reduction). Both effects were shown in other studies [70][71][72][73][74].…”
Section: Principal Resultsmentioning
confidence: 99%